Neurofibroma Type 1 with Intracranial Infiltration A Case Report - Dinar Rahmania; Agus Santoso Budi (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2017)
Neurofibromatosis (NF) is an AD dysplasi of mesoderm and ectoderm characterized by numerous neurofibromas and cafe-au-lait spot. It can develop on cranial and cavum orbita. Additional abnormalities such as episode of seizure, learning disabilities, and speech difficultie may present.  Presented a rare case that has underwent surgery by multidisciplinary team consist of neuro surgeon, plastic surgeon, and ophthalmologist. A 31 years old female patient admitted to Dr.Soetomo Hospital with mass at left face since she was 3 years old. Clinical examination shows a large plexiform mass at left hemifacial, distopia left oculi, and facial deformity. Radiological  examination shows a soft tissue mass destructing the left temporal and maxillary bone, a temporal lobe herniation to frontobasal, and a suppression on left optical nerve. In the present time, the patient is satisfied with her performance and vision. The result of surgery is satisfying. (QM 2017;01:44-47)